Worldskills Malaysia Belia 2024: showcasing excellence in restaurant service / Dr. Norhamizan Hamir, Mohd Syafiq Othman and Norliana Hashim - Hamir, Norhamizan; Othman, Mohd Syafiq; Hashim, Norliana (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
For the seventh consecutive year, the Faculty of Hotel & Tourism Management at UiTM Cawangan Pulau Pinang Kampus Permatang Pauh is honoured to host the Worldskills Malaysia Belia 2024 competition in the Restaurant Service category. This prestigious event, organised by Jabatan Pembangunan Kemahiran Malaysia runs from August 16th to 18th and highlights the growing talent in Malaysia's hospitality industry. This year's competition features six skilled contestants from various institutions across the country with four different participants from IKBN Miri Sarawak, and one each from IKBN Bandar Penawar Johor and IKBN Alor Gajah Melaka.